Organization theory an overview and an appraisal - Scott, William G. (1961)
Focuses on organization theory in management. Discussion on the classical doctrine of organization; Information on the neoclassical theory of organization; Description of the modern organization theory.
The Classical doctrine -- Neoclassical theory of organization -- Examples of the neoclassical approach to the pillars of formal organization theory -- The neoclassical view of the informal organizational --Modern organization theory -- The parts of the system and their interdependency -- The linking processes -- The goals of organization -- Organization theory: quo vadis?
Mimeographed.
Keywords: Organizational sociology; Management